Jet lag: an underestimated factor in reduced physical performance in athletes - Michał Tokarski; Angelika Tokarska; Paula Bieganek (Nicolaus Copernicus University in Toruń, 2024)
Jet lag is a common issue affecting most athletes traveling across at least 2 time zones, particularly when traveling eastward. Observational studies on over 114,000 game matches have established that traveling teams had a statistically significant higher rate of game losses. Jet lag manifests not only in a decline in athletes' physical performance but also affects cognitive abilities, attention span, and subjective feelings of fatigue. Melatonin can be a very important supplement in helping to regulate the circadian rhythm. Other recommended methods include phototherapy, appropriate meal timing, and sedative medications. This paper aims to gather the latest clinical research assessing athletes' predisposition to jet lag symptoms, large-scale retrospective observational studies evaluating this phenomenon, and discusses the functioning of the circadian rhythm, methods for alleviating jet lag symptoms, and its manifestations.